The efficacy of diode laser and subgingival air polishing with erythritol in treatment of periodontitis (clinical and microbiological study) - Sara M. A. Elmeligy; Wafaa Saleh; Gasser M. Elewa; Hani Z Abu El-Ezz; Noha Mostafa Mahmoud; Samah Elmeadawy (BMC, 2024)
Abstract Background There is insufficient clinical and microbiological evidence to support the use of diode laser and air-polishing with erythritol as supplements to scaling and root planning(SRP). The aim of the current study is to evaluate the clinical and microbiologic efficacy of erythritol subgingival air polishing and diode laser in treatment of periodontitis. Methods The study encompassed twenty-four individuals seeking periodontal therapy and diagnosed with stage I and stage II periodontitis. Eight patients simply underwent SRP. Eight more patients had SRP followed by erythritol subgingival air polishing, and eight patients had SRP followed by diode laser application. At baseline and six weeks, clinical periodontal parameters were measured, including Plaque Index (PI), Gingival Index (GI), periodontal Probing Depth (PPD), and Clinical Attachment Level (CAL). The bacterial count of Aggregatibacter actinomycetemcomitans(A.A), Porphyromonas gingivalis (P.G) was evaluated at different points of time. Results The microbiological assessment revealed significant differences in the count of A.A. between the laser and erythritol groups immediately after treatment, indicating a potential impact on microbial levels. However, the microbial levels showed fluctuations over the subsequent weeks, without statistically significant differences. Plaque indices significantly decreased post-treatment in all groups, with no significant inter-group differences. Gingival indices decreased, and the laser group showed lower values than erythritol and control groups. PPD and CAL decreased significantly across all groups, with the laser group exhibiting the lowest values. Conclusion The supplementary use of diode laser and erythritol air polishing, alongside SRP, represents an expedited periodontal treatment modality. This approach leads to a reduction in bacteria and improvement in periodontal health. Trial registration This clinical trial was registered on Clinical Trials.gov (Registration ID: NCT06209554) and released on 08/01/2024.